Pengaruh Model Student Teams Achievement Division terhadap Hasil Belajar PAI di SMP IT Al-Ghozali Jember - Damayanti, Linda; Setiawan, Bahar Agus; Putra, Dhian Wahana (Indonesian Journal Publisher, 2024)
Education aims to improve the quality of human resources. One of the efforts to enhance the quality of education is by changing the learning patterns. In schools, the learning process still revolves around the teacher with a conventional model. Therefore, the learning pattern needs to be shifted towards student-centered learning. One of the efforts to improve students' learning outcomes is for teachers to implement a cooperative learning model, such as the Student Teams Achievement Division model. The purpose of this research is to determine the impact of the Student Teams Achievement Division model on students' learning outcomes. The researcher used a quantitative research method with simple linear regression analysis by distributing questionnaires to 38 eighth-grade students. Based on the research results, it is evident that the influence of the Student Teams Achievement Division model on students' learning outcomes is 57.8%. Hence, 42.2% of students' learning outcomes are influenced by variables outside the scope of this study. In this research, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted, indicating that variable X (the Student Teams Achievement Division model) significantly affects variable Y (Students' Learning Outcomes) by 57.8%, categorized as a strong influence.